Uma proposta de avaliação da governança na gestão orçamentária dos estados brasileiros - Carneiro, Bruno de Oliveira (2018)
The study makes an evaluation proposal of the governance pattern in the budget management of the 27 (twenty seven) states with data available between 2014 and 2017, considering as a proxy to measure the governance pattern, the evolution of the budget inaccuracy of these entities in a period that incorporates the transition to the change of the government. The relevance of the budget accuracy analysis is recognized by international organizations, such as the World Bank and OECD, which have developed monitoring mechanisms of the public budget quality, such as PEFA (Public Expenditure and Financial Accountability) used in this study, complemented by unit-root econometric tests for panel data. From the imprecision measure obtained with the PEFA methodology for the variables of revenues, expenses, investments and indebtedness, the unit root tests investigated their dynamics, under the underlying hypothesis that an explosive behavior for the imprecision of fiscal variables suggests a low standard of governance in the budget management of the states. The results of the study alloweded to show a lower governance pattern on the public expenditure side, although overall, all indicators remained within a standard considered acceptable for governance in the government budget. Taken together, although the perceived lack of precision on the expenditure and investment side suggests the need to raise the governance standard in these headings overall, in the period under review, not even the change of the management seems to have compromised the state budget management.